A transient model for airflow stabilization induced by gas accumulations in a mine ventilation network. (May 2017) - Zhou, Aitao; Wang, Kai
Abstract: To analyze the airflow stabilization induced by gas accumulations in a mine ventilation network, a transient model for airflow caused by gas accumulations is presented. The Runge Kutta method is selected to solve this model. To quantify the average gas density in the transient model, a solution to the gas diffusion equation in airways is interpreted. The Crank-Nicholson difference method is applied to calculate the gas diffusion equation, and the chase method is selected to calculate the gas concentration distribution in airways. Furthermore, a coupled solution between the transient model and the gas diffusion equation is proposed, and a transient airflow ventilation network program for this coupled solution is developed. According to the simulations conducted in this work, it is concluded that the results agree well with the field test. Finally, it was found that gas accumulation in inclined airways can generate gas ventilation pressure, which can lead to airflow disorder. Highlights: A transient model for airflow induced by gas accumulations is established. The solution to the gas diffusion equation in airways is interpreted. A transient airflow ventilation network program for this coupled solution is developed. Gas accumulation in inclined airways can generate gas ventilation pressure.